Impact of Ramadan Fasting on Dietary Intakes Among Healthy Adults: A Year-Round Comparative Study - Shatila, Hibeh; Baroudi, Mariam; El Sayed Ahmad, Raeda; Chehab, Rana; Forman, Michele R.; Abbas, Nada; Faris, MoezAlIslam; Naja, Farah (Frontiers in Nutrition, 2021)
Religious rituals are considered among the principle factors that impact dietary behaviors and food selections. The main objective of this study is to characterize food intake among Lebanese adults observant of the fasting month of Ramadan and compare it to their intake of the rest of the year. During a year-round study, including the month of Ramadan, Lebanese adults (n=62), completed multiple (9 to 13) 24-hour dietary recalls. Information about sociodemographic and lifestyle characteristics was also obtained. Dietary intake was examined using food groups as well as energy, macro, and micronutrient consumption. Significant differences in dietary intakes were observed for 13 of the 19 food groups (expressed as a percent of total energy) during Ramadan as compared to the rest of the year. More specifically, the intakes of cereals, cereal-based products, pasta, eggs, nuts and seeds, milk and dairy, and fats and oils were lower, while vegetables, dried fruit, Arabic sweets, cakes and pastries, and sugar-sweetened-beverages intakes were higher during Ramadan as compared to the remainder of the year (p<0.05). Such differences in food groups’ intakes were reflected in nutrients intakes, including carbohydrates, cholesterol, calcium, beta-carotene, vitamin C, folate, and magnesium. The findings of this study highlighted major differences in dietary intakes between the fasting month as compared to the rest of the year. With the large number of adults who observe fasting during Ramadan, the particularities of dietary intake during Ramadan ought to be considered in the development of context and culture-specific dietary recommendations.